Implementation of Digitalization of Bookkeeping Based on Accounting Computerization: Case Study From Village-Owned Enterprise (BUMDES) Ngargoretno, Salaman, Magelang, Indonesia - Thoha, Muhammad Nuur Farid; Ismiati, Mia (Manunggal Halim Jaya, 2025)
This study examined the implementation of Microsoft Excel-based bookkeeping digitalization in the Ngargoretno Village-Owned Enterprise (BUMDes) for the 2023 period. The sample used in this study was the Ngargoretno BUMDes, which oversees seven small and medium enterprises (SMEs): Kopi Merah, Kopi Liar, Kopi Arabica, Gula Semut, Teh Sangit, Jahe Instan, and Kunyit Instan. This research employed a qualitative descriptive approach with a case study focus. The findings indicate that the digitalization of bookkeeping has positively impacted the quality of financial recordkeeping within Ngargoretno BUMDes. The new system has made the bookkeeping process more informative and has significantly helped the BUMDes management overcome the challenges previously faced.